Primary care disease management for venous leg ulceration in german healthcare: results of the Ulcus Cruris Care pilot study - Senft, Jonas; Fleischhauer, Thomas; Poß-Doering, Regina; Frasch, Jona; Feißt, Manuel; Awounvo Awounvo, Junior Sinclair; Müller-Bühl, Uwe; Altiner, Attila; Szecsenyi, Joachim; Laux, Gunter (Healthcare, 2023)
Despite proven effectiveness, compression therapy is applied in only 20-40% of patients with venous leg ulceration, leading to avoidable chronification and morbidity. The Ulcus Cruris Care project was established to develop a new disease-management concept comparable to existing programs for chronic diseases to support evidence-based treatment of venous leg ulceration. This prospective controlled study assessed its first implementation. Interventional elements comprised online training for general practitioner practices, software support for case management, and educational materials for patients. A total of 20 practices and 40 patients were enrolled in a 1:1 ratio to the intervention and control group. Guideline-conform compression therapy was applied more frequently in the intervention group (19/20 [95%] vs. 11/19 [58%]; p = 0.006). For patients with ulcers existing ≤ 6 months, the healing rate at 12 weeks was 8/11 [73%] (intervention) compared to 4/11 [36%] (control; p = 0.087). Patients after intervention had higher scores for self-help and education in the PACIC-5A questionnaire (42.9 ± 41.6 vs. 11.4 ± 28.8; p = 0.044). Treatment costs were EUR 1.380 ± 1.347 (intervention) and EUR 2.049 ± 2.748 (control; p = 0.342). The results of this study indicate that the Ulcus Cruris Care intervention may lead to a significant improvement in care. Consequently, a broader rollout in German healthcare seems warranted.